2016
DOI: 10.1096/fj.201600453r
|View full text |Cite
|
Sign up to set email alerts
|

In vitro model for DNA double‐strand break repair analysis in breast cancer reveals cell type–specific associations with age and prognosis

Abstract: Dysfunction of homologous recombination is a common denominator of changes associated with breast cancer-predisposing mutations. In our previous work, we identified a functional signature in peripheral blood lymphocytes from women who were predisposed that indicated a shift from homologous recombination to alternative, error-prone DNA double-strand break (DSB) repair pathways. To capture both hereditary and nonhereditary factors, we newly established a protocol for isolation and ex vivo analysis of epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…Breast cancer cell lines were grown on cover slips, fixed with 3.7% formaldehyde in PBS, permeabilized with 0.5% TritonX-100, and incubated with antibodies and nuclear DAPI-stain as described in Deniz et al [49]. Primary antibodies used for immunostaining were polyclonal rabbit antibodies against 53BP1 (NB100-304, Novus Biologicals) and mouse mAb anti-phospho-Histone H2A.X (Ser139, clone JBW301, Invitrogen, Darmstadt, Germany).…”
Section: Quantitative Immunofluorescence Microscopymentioning
confidence: 99%
“…Breast cancer cell lines were grown on cover slips, fixed with 3.7% formaldehyde in PBS, permeabilized with 0.5% TritonX-100, and incubated with antibodies and nuclear DAPI-stain as described in Deniz et al [49]. Primary antibodies used for immunostaining were polyclonal rabbit antibodies against 53BP1 (NB100-304, Novus Biologicals) and mouse mAb anti-phospho-Histone H2A.X (Ser139, clone JBW301, Invitrogen, Darmstadt, Germany).…”
Section: Quantitative Immunofluorescence Microscopymentioning
confidence: 99%
“…In our study presented here, we did not obtain evidence for altered PARP inhibitor responsiveness in PBLs from high-risk individuals or ovarian cancer patients as compared to healthy controls. Previously, we observed a highly significant response in homozygously BRCA1 - or BRCA2 -mutated cells, but either failed to detect a significant change or determined marginally significantly reduced IC50 values in heterozygously BRCA1 -, BRCA2 - and PALB2 - mutated cells [ 21 , 25 ]. In agreement with our findings, clinical PARP inhibitor use was originally based on the concept that loss of the wild-type BRCA allele represents an obligatory step for specific tumor cell killing [ 53 ].…”
Section: Discussionmentioning
confidence: 86%
“…Changes in various DNA repair genes in tumor biopsies were further demonstrated to correlate with clinical PARP inhibitor responses in metastatic prostate cancer patients [ 27 ]. In our previous studies, we demonstrated increased sensitivity to PARP inhibitor 1,5-isoquinolinediol (IQD) in immortalized lymphocytes (LCLs) with homozygously mutated BRCA2 and in mammary epithelial cells with homozygously mutated BRCA1 [ 21 , 25 ]. Therefore, we asked whether DSB repair defects in our case groups as indicated by SSA increases also translate into altered responses to the PARP inhibitor IQD in PBLs (Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential effect of Alt-EJ and PARP-1 on breast cancer development and progression has been the subject of few studies, although it could be an important mechanism. Alt-EJ is an extremely error-prone DNA repair pathway that has elevated activity in high-risk breast cancer (27) and breast cancer is one of the most genomically unstable cancers. PARP-1 inhibition is effective in breast cancer therapy, especially in patients with BRCA1/2 mutations.…”
Section: Discussionmentioning
confidence: 99%